Review of Latest Advancements and Trends in Machine Learning - K, Vinod Kumar; P, Santosh Kumar (International Journal of Computer Sciences and Engineering, 2019)
In this paper, various machine learning algorithms have been discussed. These algorithms are used for various purposes like data mining, image processing, predictive analytics, etc. to name a few. The main advantage of using machine learning is that, once an algorithm learns what to do with data, it can do its work automatically.